Tinjauan Yuridis Terhadap Sertifikat Hak Atas Tanah Ganda (Overlapping) di Badan Pertanahan Nasional Kabupaten Gorontalo - Siti Maryam Nasir (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This study aims to identify and analyze the legal implications associated with the ownership of overlapping land certificates concerning Decision Number 4/G/2021/PTUN-G, as well as to evaluate the responsibilities of the National Land Agency (BPN) regarding these overlapping certificates. This study employs an empirical method based on human behavior, gathering verbal data through interviews and actual behavior through direct observation. Study findings in the last five years, from 2020 to 2024, indicate that several complaints have been reported to the Gorontalo Regency Land Office regarding the issuance of overlapping certificates. The study's findings suggest that five complaints reached mediation, while one case escalated to court, specifically through Decision Number 4/G/2021/PTUN-GTO. This decision pertains to a land dispute between Mr. Arudji Gobel and Mrs. Ratna M. L. Datau in Ulapato Village, Telaga Biru Subdistrict, Gorontalo Regency, involving the issuance of overlapping certificates. Contributing factors to the overlapping certificates include public misunderstanding, informal sales, lack of available data at the village level, and legal and administrative loopholes. These issues result in a lack of legal certainty, as the primary aim of land registration is to obtain certificates as valid proof of ownership. The responsibility for overlapping certificates lies with the National Land Agency (BPN), which must verify both physical and legal data prior to issuing certificates. In the event of overlapping certificates, the National Land Agency (BPN) is required to annul one of the certificates. If any error or maladministration by National Land Agency (BPN) staff is discovered, they may face criminal or civil penalties. Even without maladministration or errors, the National Land Agency (BPN) remains responsible for resolving such issues. With clear legal regulations, affected parties can assert their rights through legal channels.